2021
DOI: 10.1002/jmv.27123
|View full text |Cite
|
Sign up to set email alerts
|

The demographic characteristics, prognosis, and relationship with cancer subtypes of hospitalized COVID‐19 patients with malignancy: A single‐center experience

Abstract: Undoubtedly, cancer patients have suffered the most from the COVID‐19 pandemic process. However, cancer is a heterogeneous disease, and each patient has responded differently to COVID‐19. We aimed to describe the clinical characteristics and outcomes of patients with cancer and COVID‐19. We retrospectively reviewed 45 cancer patients hospitalized in the Cerrahpaşa Medical Faculty COVID‐19 department from March 23 to October 23, 2020. We analyzed the demographic characteristics, symptoms, laboratory findings, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Thrombocytopenia in cancer children is understudied, but a low count in adults was associated with coagulation disorders that lead to organ failure and death in patients with severe COVID-19 ( 13 18 ). In adult patients with hemato-oncological diseases and COVID-19, results were similar to the ones found in adults free of cancer ( 19 , 20 ).…”
Section: Discussionsupporting
confidence: 84%
“…Thrombocytopenia in cancer children is understudied, but a low count in adults was associated with coagulation disorders that lead to organ failure and death in patients with severe COVID-19 ( 13 18 ). In adult patients with hemato-oncological diseases and COVID-19, results were similar to the ones found in adults free of cancer ( 19 , 20 ).…”
Section: Discussionsupporting
confidence: 84%
“…After that, 300 articles were evaluated for full-text eligibility, and 197 articles with available data but not Asian were excluded. Ultimately, 103 studies conducted in Asia were enrolled in this meta-analysis [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Resultsmentioning
confidence: 99%
“…Findings accumulated since the pandemic suggest that cancer patients are at a higher risk for COVID-19 infections and have higher morbidity and mortality than the general population [ 11 ]. In a study involving 28 cancer patients, it was observed that these patients had twice the risk of COVID-19 infections when compared to the general population [ 12 ].…”
Section: Discussionmentioning
confidence: 99%